Key Factors to Consider When Selecting a Site for Building a House in Northern Thailand - Suchat Tachaudomdach (Journal of Research in Social Science and Humanities, 2024)
Selecting an appropriate site for building a house is a critical decision that impacts the long-term satisfaction, safety, and financial investment of homeowners. This paper explores the key factors that should be carefully evaluated during the site selection process. These factors include direction and location of house, neighborhood, topography and soil quality, climate and environmental consideration, utilities and infrastructure, access and transportation, cost of land and budget, aesthetic and lifestyle preferences, privacy and noise levels, and cultural and traditional beliefs. By systematically considering these factors, prospective homeowners can make informed decisions that align with their lifestyle needs and future aspirations, ensuring a harmonious and sustainable living environment.